Implementasi Pendidikan Karakter untuk Membentuk Akhlakul Karimah di MTs Negeri 1 Purworejo Tahun Pelajaran 2018/2019: Pendidikan Karaker, Akhlakul Karimah (JURNAL ILMIAH TUT WURI HANDAYANI, 2023)
This study aims to examine the implementation of character education to form the moral character of MTs Negeri 1 Purworejo. The objectives of this study were (1) to determine the management of character education including planning, implementation, supervision, evaluation at MTs Negeri 1 Purworejo, (2) to determine the supporting and inhibiting factors of Character education at MTs Negeri 1 Purworejo, (3) to uncover results implementation of character education at MTs 1 Purworejo. This type of research is qualitative descriptive. The location of this study was at MTs Negeri 1 Purworejo. The data sources in this study are two sources of data, primary data, namely the head of the madrasa, deputy head of the madrasa, teachers, and students while secondary data is an RPP document related to the object under study. The results of this study through observation, interviews and documentation. The next data is analyzed qualitatively using triangulation to ensure the validity of the data on the focus under study. The research phase through planning, organizing, implementing, monitoring and evaluating. The implementation of character education also has two supporting factors: character / heredity, personality, family, teacher / educator. Inhibiting factors: limited time in the madrasa, the busyness of parents, attitudes of parents, the environment and the mass media. The results showed that the character education values integrated in the learning process activities were religious, disciplined, diligent, curiosity, caring, and responsibility, intelligent, independent cooperation. While the implementation of character education in extracurricular activities is carried out through scout activities, KIR, Bording School, PBB / paskibraka, rebana, UKS, PMR, so that the character of discipline, independence, democracy, national spirit, environmental care, social care, responsibility, reading pleasure , skilled in organization by providing motivation, understanding, advice, sanctions, and exemplary and habituating through smiles, shaking hands, do, together with trash picking.